FACTORS DETERMINING THE SUBMISSION’S PROMPTNESS OF FINANCIAL STATEMENT - Muthia Harnida (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research aims at identifying the factors determining the submission’s promptness of financial statement by examining whether the managerial ownership, institutional ownership, independent commissioner, audit committee and profitability affect the promptness of the company for submission of financial statement according to the regulation issued by Bapepam. Besides, the research also examines whether the promptness of company for submission of annual report differs from midyear report. The research sample is manufacturing companies listed in Indonesian Stock Exchange for the period of 2012-2014 with 61 observations. The hypothesis testing is to examine whether there is a difference between the annual report’s submission and the midyear report submission. The result shows that statistically there is a significant difference between the submission’s promptness of the annual report and the midyear report. The result indicates that the submission of midyear report is faster than the annual report. The hypothesis testing is also to examine the effects of managerial ownership, institutional ownership, independent commissioner, audit committee and profitability used the multiple regression analysis. The results indicate that only managerial ownership and institutional ownership have significant effect on the submission’s promptness of financial statement. In contrast, the variables of independent commissioner, audit committee and profitability have no significant effect on the submission’s promptness of financial statement.